Front office procedures - Kasavana, Michael L.; Brooks, Richard M. (East Lansing, Michigan Educational Institute of the American Hotel & Motel Association, 1995)
This book includes the world of hotels, the guest cycle, front office management
Includes bibliographical references and index
Keywords: Quản trị khách sạn